Update on the causes, investigation and management of empyema in childhood. Issue 5 (24th August 2010) - Walker, Woolf; Wheeler, Robert; Legg, Julian
Abstract : Despite being recognised for over two millennia and having an increasing incidence in many countries, the management of childhood empyema remains controversial. This review examines the recent literature on its causes and investigation then focuses on its treatment. Following a trial of appropriate intravenous antibiotics, the evidence would currently support the use of chest drain insertion with urokinase instillation as first line treatment with video-assisted thoracoscopic surgery to be used for failure of medical management. A treatment algorithm is proposed to guide clinical practice.